Low-dose and standard-dose ticagrelor compared with clopidogrel in patients with acute coronary syndromes: A cohort study from china - Peng, Wenxing; Zhang, Yunnan; Lin, Yang (Frontiers in Cardiovascular Medicine, 2022)
Purpose: Previous trials have demonstrated that ticagrelor was superior to clopidogrel in acute coronary syndrome (ACS) patients. However, several recent studies showed that ticagrelor was associated with a significantly higher risk of bleeding compared with clopidogrel, especially in East Asian patients. Low-dose ticagrelor might improve the safety of ACS patients in the Chinese population. Therefore, this study mainly explored the low-dose ticagrelor in Chinese ACS patients. Methods: A total of 199 ACS patients were enrolled in this study. Platelet function was assessed after at least 1 month of dual antiplatelet therapy in all patients. The maximum platelet aggregation rate induced by adenosine-5-diphosphate (ADP) was detected by light transmittance aggregometry (LTA). Platelet aggregation rate induced by ADP of more than or equal to 42.9% was defined as high on-treatment platelet reactivity (HPR) to P2Y12 inhibitors. All patients were followed up for at least 12 months. Clinical outcomes, changes of antiplatelet regimen, medication compliance and adverse reactions were collected Results: Patients were divided into three groups according to the P2Y12 inhibitors, including 87 cases in clopidogrel (75 mg once a day) group, 41 cases in ticagrelor 60 mg (twice a day) group, and 71 cases in ticagrelor 90 mg (twice a day) group. ADP-induced platelet aggregation rates in ticagrelor 60 mg group and 90 mg group were 28.4 (19.6, 42.9) and 22.33 (15.1, 34.7) respectively, which were significantly lower than those in clopidogrel group 49.3 (36.5, 61.0) with adjusted p＜0.001. At the same time, there was no significant difference in ADP-induced platelet aggregation rate between ticagrelor 60 mg and 90 mg group (adjusted P=0.105). Compared with clopidogrel, the proportion of normal on-treatment platelet reactivity (NPR) of ticagrelor 60 mg and ticagrelor 90 mg were significantly higher than that of clopidogrel, and the proportion of NPR of ticagrelor 90 mg group was significantly higher than that of ticagrelor 60 mg group. Conclusions: Patients of ticagrelor 60 mg and ticagrelor 90 mg had comparable platelet aggregation rates induced by ADP. And low-dose ticagrelor might be an alternative for antiplatelet therapy in patients with ACS.